PENYULUHAN LITERASI MEDIA INTERNET DAN TELEPONGENGGAMDI DUSUN BANDUNG DAN DUSUN SONGBANYU 1, DESA SONGBANYU,KECAMATAN GIRI SUBO, GUNUNG KIDUL,DAERAH ISTIMEWA YOGYAKARTA - Muntoha Muntoha (UII, 2015)
In the era of globalization and information disclosure as at present, the developmentof technology, internet, media, and the media can not be separated from the developmentof a country. Everything will evolve simultaneously and in tandem. This brings a lot ofbenefits and convenience. However,on the other hand also brings many negative effects,especially if used by children who do not understand what is good and what is bad.Misinformation and distorted their reading often becomes food. On the other hand,technological developments bring, they are able to have high-tech devices, such assmartphones. In response to this, the author took the initiative to provide an extensionof the mass media and internet literacy at Dusun Bandung and Dusun Songbanyu 1, DesaSongbanyu, Kecamatan Giri Subo, Gunung Kidul, Daerah Istimewa Yogyakarta. With hope,the children become better understood and more stringent parents supervise what theirchildren get through the disclosure of information and the development of technologytoday.